2003
DOI: 10.1080/07315724.2003.10719319
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of a Dietary Supplement Containing Dehydroepiandrosterone (DHEA) and Androstenedione Has Minimal Effect on Immune Function in Middle-Aged Men

Abstract: These findings suggest that, although chronic intake of a complex dietary supplement containing DHEA, androstenedione and herbal extracts increases serum androgen levels, it has minimal effect on immune function in middle-aged men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…An increase in the serum concentrations of androstenedione (342%), free testosterone (38%), dihydrotestosterone (71%), and estradiol (103%) has been determined at unchanged total testosterone. In another study the effects of a dietary supplement containing dehydroepiandrosterone, androstenedione and herbal extracts (TT including) on immune function in middle-aged men had indicated that this supplement had minimal effect on men immune function, but significantly increased serum levels of androstenedione, free testosterone, and estradiol (Kohut et al, 2003).…”
Section: Results Versus Past Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…An increase in the serum concentrations of androstenedione (342%), free testosterone (38%), dihydrotestosterone (71%), and estradiol (103%) has been determined at unchanged total testosterone. In another study the effects of a dietary supplement containing dehydroepiandrosterone, androstenedione and herbal extracts (TT including) on immune function in middle-aged men had indicated that this supplement had minimal effect on men immune function, but significantly increased serum levels of androstenedione, free testosterone, and estradiol (Kohut et al, 2003).…”
Section: Results Versus Past Studiesmentioning
confidence: 97%
“…Although different effects of TT on animals (Gauthaman et al, 2002;Gauthaman et al, 2003;Arcasoy et al, 1998) and men (Brown et al, 2000;Brown et al, 2001;Kohut et al, 2003;Antonio et al, 2000) have been evaluated and many active compounds from TT extract have been established (Huang et al, 2003;De Combarieu et al, 2003;Cai et al, 2001;Conrad et al, 2004) the mode of its action and efficacy remains uncertain and controversial. It is widely believed that TT affects strongly the androgen metabolism increasing significantly testosterone or testosterone precursor levels.…”
Section: Introductionmentioning
confidence: 98%
“…The second part of this review aims to summarise recent studies performed in both rodents [22,[82][83][84][85][86][87][88][89][90][91], and humans [92][93][94][95][96][97][98][99][100][101][102][103][104][105], that have investigated whether DHEA supplementation can reverse the immune dysregulation that occurs coincident with DHEA deficiency.…”
Section: Dhea Supplementationmentioning
confidence: 99%
“…The authors concluded that this supplement does not contain any indirect or direct testosterone-enhancing properties. In fact, the only adequate clinical trials where a dose of Tribulus (750 mg or more) appears to increase testosterone is when it is combined with 150 mg of DHEA and 300 mg of androstenedione [224][225][226][227]. And drops of 5.0 mg/ dl in HDL or "good cholesterol" were observed which have to be somewhat concerning [225], but again was probably due to the DHEA and androstenedione components.…”
Section: Tribulus Terrestrismentioning
confidence: 87%